Prevalence of Nonalcoholic Fatty Liver Disease in Patients With Rheumatoid Arthritis: A Systematic Review and Meta-analysis - Zamani, Mohammad; Alizadeh-Tabari, Shaghayegh; Chitkara, Puja; Singh, Siddharth; Loomba, Rohit (Clinical gastroenterology and hepatology, 2023)
Previous studies have shown a potential association between nonalcoholic fatty liver disease (NAFLD) and some immune-mediated inflammatory diseases, such as rheumatoid arthritis (RA), but this association has not been analyzed systematically. Therefore, we aimed to perform a systematic review and meta-analysis to ascertain a pooled prevalence estimate of NAFLD among patients with RA to fill this gap in knowledge. We conducted a literature search in PubMed, Embase, Web of Science, Scopus, and ProQuest, for observational studies published from inception to August 31, 2022, which reported prevalence of NAFLD in 100 or more adult (age, ≥18 y) patients with RA. To be included, NAFLD diagnosis was based on either imaging or histologic assessment. The results were presented as pooled prevalence, odds ratio, and 95% CI. The I2 statistic was used to measure the heterogeneity between studies. This systematic review included 9 eligible studies derived from 4 continents comprising 2178 patients (78.8% women) with RA. The pooled prevalence of NAFLD was 35.3% (95% CI, 19.9–50.6; I2 = 98.6%; P < .001) in patients with RA. All studies used ultrasound for the diagnosis of NAFLD, except for 1 study that used transient elastography. The pooled prevalence of NAFLD in men with RA was significantly higher than in women with RA (35.2%; 95% CI, 24.0–46.5 compared with 22.2%; 95% CI, 17.9–26.58; P for interaction = .048). Each 1-unit increase in body mass index was associated directly with a 24% increased risk of NAFLD in RA patients (adjusted odds ratio, 1.24; 95% CI, 1.17–1.31; I2 = 0.0%; P = .518). Based on this meta-analysis, 1 in 3 patients with RA had NAFLD, which appears comparable with its overall prevalence among the general population. Clinicians should actively screen for NAFLD in patients with RA.